Оцінка невизначеності результатів вимірювань кондуктивного паразитного випромінювання методом прямого зчитування - Штефан, І. Ю. (ХНУРЕ, 2019)
The given work is devoted to the development of a procedure of estimating of uncertainty of measurements. The model equation is recorded, the numerical values of the input values are estimated, the numerical value of the measured value is calculated, the standard uncertainties of the input quantities, the sensitivity coefficients, the total standard uncertainty, and the expanded uncertainty are estimated. The uncertainty budget is given.